Mechanically driven Li dendrite penetration in garnet solid electrolyte - Yuwei Zhang; Soroush Motahari; Eric V. Woods; Stefan Zaefferer; Peter Schweizer; Zhiyuan Zhang; Yuqi Liu; Baptiste Gault; Franz Roters; Dierk Raabe; Christina Scheu; Yug Joshi; et al. (Nature, 2026)
Abstract All-solid-state batteries promise improved safety and higher energy density by replacing flammable liquid electrolytes and graphite anodes with solid electrolytes and lithium metal 1–4 . However, the penetration of soft lithium dendrites into hard ceramic electrolytes remains a substantial obstacle to realizing all-solid-state lithium metal batteries 5–7 . The mechanism by which mechanically soft lithium dendrites fracture hard ceramic electrolytes remains under debate 7–10 owing to the challenges of characterizing nanoscale lithium distribution and its microstructure at the dendrite tip 11 . Here we investigate the fracture process driven by lithium dendrites in garnet electrolytes using multiscale cryogenic electron microscopy and micromechanical fracture models. We directly visualize lithium dendrites fully filling nanoscale crack tips and extending into micrometre-scale cracks. Limited crystal lattice rotation and plasticity in lithium dendrites indicate that the plated lithium generates substantial hydrostatic stress, which induces tensile stress in the solid electrolyte and drives both intergranular and transgranular fracture. By contrast, the region ahead of the lithium dendrite tip shows no measurable enrichment of lithium or lithium metal nuclei. The mechanically driven lithium penetration in garnet solid electrolyte can be redirected by geometrically engineered voids in the electrolyte, thus mitigating short-circuiting. Our findings suggest that grain boundary toughening and defect engineering are effective strategies for designing dendrite-resistant solid electrolytes.